Antiurolithic effect of olive oil in a mouse model of ethylene glycol-induced urolithiasis - Mohammed Alenzi (Investigative and Clinical Urology, 2017)
Purpose: At present, commercially available antiurolithic drugs have more adverse effects than potential therapeutic or preventive effects with chronic use. With this in mind, the present study was designed to assess the antiurolithic effect of olive oil in a mouse model of ethylene glycol (EG)-induced urolithiasis. Materials and Methods: Adult albino mice were divided into 6 groups. Group I was fed the vehicle only. Group II was supplemented with 0.75% EG alone in drinking water during the experimental period to initiate deposition of calcium oxalate in kidneys, which leads to urolithiasis in animals. Groups III (olive oil control group) through V were fed olive oil orally at various doses during the experimental period. Group VI received cystone (750 mg/kg). Groups IV–VI additionally received 0.75% EG in drinking water ad libitum. SPSS ver.17.0 was used for statistical analysis. Results: The study results showed significantly higher levels of serum urea, uric acid, and creatinine (p<0.05) in group II than in groups III–VI and I. Administration of olive oil at different doses restored the elevated serum parameters in groups IV and V compared with group II. Urine and kidney calcium, oxalate, and phosphate levels in groups IV–VI were significantly lower (p<0.05) than in animals with EG-induced urolithiasis (group II). Group V mice showed a significant restoration effect on serum as well as urine and kidney parameters compared with group II. Conclusions: Supplementation with olive oil (1.7 mL/kg body weight) reduced and prevented the growth of urinary stones, possibly by inhibiting renal tubular membrane damage due to peroxidative stress induced by hyperoxaluria.